Optimasi Formula Kapsul Ekstrak Temu Putih (Curcuma zedoaria) dengan Variasi Bahan Penghancur. - Muharromah, Wini Aulia Ika; Rini, Tri Diana Puspita (Usadha, 2025)
Cancer is one of the most common causes of death in the world. Based on data from the World Health Organization (WHO), the number of cancer patients worldwide increases by 6.25 million people, or about 12% of the global population each year. White turmeric contains turmerone, essential oil, and curcuminoids. Curcuminoids have activity against P-388 murine leukemia cells and can inhibit the growth of cancer cells. One of the solid pharmaceutical preparations that is often used is capsules. Capsules require a quick disintegration time immediately after swallowing, and they must be absorbed in the digestive tract to provide bioavailability effects. Therefore, additional materials are needed for the capsule to dissolve quickly after contact with gastric fluid. The population in this study consists of disintegrating agents with various brands. The samples used were sodium starch glycolate, Ac-Di-Sol, and SD600 with a concentration of 4%. The research used an experimental method with a post-test control group design, with four formulations with different disintegrant materials. (sodium starch glycolate, Ac-Di-Sol, dan SD600). The research results show that all formulations meet the requirements for physical quality tests of capsules except for the flow rate test. There is a significant difference between the disintegration time of formula 3 with SD600 and the disintegration time of formula 4 with Ac-Di-Sol. Formula 4 with the disintegrant Ac-Di-Sol has the fastest disintegration time, 15.70 minutes. The factors that influence the results are the moisture and hygroscopicity of the powder.